Peace and conflict : the South Asian experience - Upadhyaya, Priyankar, 1954-; Kumar, Samrat Schmiem (New Delhi : Foundation Books, 2014)
South Asia's diversity is also reflected in the many violent inter-state and intra-state conflicts that further distinguish it from other regions of the world. Despite the national differences, one can still find transnational commonalities in cultures, languages and religions, bound together by the common pre-colonial and colonial history of the South Asian countries. This book takes its readers into a'reflexive journey' of understanding peace in South Asia, and the imperceptible way through which religious and cultural dimensions contribute to the peace building process. It also unravels the unique patterns of common cultural practices in the region to emphasize that the connect between cultures can ever be a source of tension as well as reward. In addition, it presents a fascinating account of the origins and meaning of the concept of ahimsa in Buddhism and Jainism, and looks at the practical examples of ahimsa from India to highlight the diversity of peace, non-violence and peace work that exist in the country. One of the chapters offers an intriguing example of nonviolent resistance in Pakistan - it documents the history of a nonviolent civil resistance movement, the'lawyer's movement', or also known as the'Black Revolution', for justice and the rule of law in Pakistan.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Peace-building -- South Asia; Peace; South Asia -- Politics and government; South Asia -- Social conditions